Occurrence, functionality and abundance of the TERT promoter mutations - Rachakonda, Sivaramakrishna; Hoheisel, Jörg D; Kumar, Rajiv (International journal of cancer, 2021)
Telomere shortening at chromosomal ends due to the constraints of the DNA replication process acts as a tumor suppressor by restricting the replicative potential in primary cells. Cancers evade that limitation primarily through the reactivation of telomerase via different mechanisms. Mutations within the promoter of the telomerase reverse transcriptase (TERT) gene represent a definite mechanism for the ribonucleic enzyme regeneration predominantly in cancers that arise from tissues with low rates of self-renewal. The promoter mutations cause a moderate increase in TERT transcription and consequent telomerase upregulation to the levels sufficient to delay replicative senescence but not prevent bulk telomere shortening and genomic instability. Since the discovery, a staggering number of studies have resolved the discrete aspects, effects and clinical relevance of the TERT promoter mutations. The promoter mutations link transcription of TERT with oncogenic pathways, associate with markers of poor outcome and define patients with reduced survivals in several cancers. In this review, we discuss the occurrence and impact of the promoter mutations and highlight the mechanism of TERT activation. We further deliberate on the foundational question of the abundance of the TERT promoter mutations and a general dearth of functional mutations within noncoding sequences, as evident from pan-cancer analysis of the whole-genomes. We posit that the favorable genomic constellation within the TERT promoter may be less than a common occurrence in other noncoding functional elements. Besides, the evolutionary constraints limit the functional fraction within the human genome, hence the lack of abundant mutations outside the coding sequences.
Keywords: aktivace transkripce; stárnutí buněk; mutace; telomerasa; Neoplasms; Telomere Shortening; nestabilita genomu; telomeres; Transcriptional Activation; promotorové oblasti (genetika); Cellular Senescence; cancers; Genomic Instability; zkracování telomer; lidé; Telomerase; telomerase; TERT promoter mutations; Humans; telomery; Promoter Regions, Genetic; nádory; Mutation; Telomere